Supporting the establishment of the Caribbean Public Health Agency : healthier, happier horizons for all (CARICOM Secretariat GeorgetownGY, 2010)
Presents an outline of the Caribbean Public Health Agency (CARPHA; its origins, objectives, expected output and its role within the Caribbean Community's (CARICOMs) regional health strategy - the Caribbean Cooperation in Health III (CCHIII) framework.
Keywords: HEALTH ADMINISTRATION